Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.2 - Solving Quadratic Equations by Completing the Square - Exercise Set - Page 775: 11



Work Step by Step

$3m^{2}-7m=3$ Take the $3$ to the left side of the equation: $3m^{2}-7m-3=0$ Use the quadratic formula to solve the equation. The formula is $m=\dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}$. For this equation, $a=3$, $b=-7$ and $c=-3$ Substitute: $m=\dfrac{-(-7)\pm\sqrt{(-7)^{2}-4(3)(-3)}}{2(3)}=\dfrac{7\pm\sqrt{49+36}}{6}=...$ $...=\dfrac{7\pm\sqrt{85}}{6}=\dfrac{7}{6}\pm\dfrac{\sqrt{85}}{6}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.